Functional role of DNA mismatch repair gene PMS2 in prostate cancer cells - Fukuhara, Shinichiro (Oncotarget, 2015)
DNA mismatch repair (MMR) enzymes act as proofreading complexes that maintains genomic integrity and MMR-deficient cells show an increased mutation rate. MMR has also been shown to influence cell signaling and the regulation of tumor development. MMR consists of various genes and includes post-meiotic segregation (PMS) 2 which is a vital component of mutL-alpha. In prostate, the functional role of this gene has never been reported and in this study, our aim was to investigate the effect of PMS2 on growth properties of prostate cancer (PCa) cells. Previous studies have shown PMS2 to be deficient in DU145 cells and this lack of expression was confirmed by Western blotting whereas normal prostatic PWR-1E and RWPE-1 cells expressed this gene. PMS2 effects on various growth properties of DU145 were then determined by creating stable gene transfectants. Interestingly, PMS2 caused decreased cell proliferation, migration, invasion, and in vivo growth; and increased apoptosis as compared to vector control. We further analyzed genes affected by PMS2 expression and observe the apoptosis-related TMS1 gene to be significantly upregulated whereas anti-apoptotic BCL2A1 was downregulated. These results demonstrate a functional role for PMS2 to protect against PCa progression by enhancing apoptosis of PCa cells.